2006
DOI: 10.1016/j.nuclphysa.2006.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Diquark Bose–Einstein condensation and nuclear matter

Abstract: We study a possible transition between symmetric nuclear matter and the diquark Bose-Einstein condensate (BEC) matter at zero temperature. We find that chiral restoration transition is first order and coincides with deconfinement. We investigate various possible coexistence patterns which may emerge from the first order deconfinement phase transition by assuming different values for the critical deconfinement chemical potential. If deconfinement takes place at higher chemical potential, there exists a mixed ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…It is a demanding task to develop unified approaches for quark/nuclear matter on the basis of chiral quark models in which nucleons and mesons appear as relativistic bound states of quarks and antiquarks (for first steps in this direction, see Ref. [49,50]). Under conditions of high density and/or temperature these bound states dissociate into continuum correlations (resonances) in quark matter within a Mott transition (see [51] for a model calculation within a nonrelativistic Green functions approach, which has also lead to an early prediction of stable quark matter cores in compact stars [52]).…”
Section: Discussionmentioning
confidence: 99%
“…It is a demanding task to develop unified approaches for quark/nuclear matter on the basis of chiral quark models in which nucleons and mesons appear as relativistic bound states of quarks and antiquarks (for first steps in this direction, see Ref. [49,50]). Under conditions of high density and/or temperature these bound states dissociate into continuum correlations (resonances) in quark matter within a Mott transition (see [51] for a model calculation within a nonrelativistic Green functions approach, which has also lead to an early prediction of stable quark matter cores in compact stars [52]).…”
Section: Discussionmentioning
confidence: 99%
“…The scenario that we have in mind is similar to as in Ref. [5], where, as the baryon density is increased, the baryonic matter undergoes a phase transition to diquark BEC phase. The transition from BCS to BEC is most likely to be a crossover similar to their non relativistic counterparts in condensed matter systems like cold fermionic atoms.…”
Section: Introductionmentioning
confidence: 89%
“…Several recent studies have shown the advantages of using composite nucleons in finite density calculations [1], [2], [3]. For example, in some models the saturation mechanism of the system can be related to how the structure of the nucleon changes with density [4].…”
Section: Introductionmentioning
confidence: 99%